Effects of SGLT2 inhibitors on stroke and its subtypes in patients with type 2 diabetes: a systematic review and meta-analysis - Wen-Hsuan Tsai (Nature Portfolio, 2021)
Abstract Sodium-glucose cotransporter 2 (SGLT2) inhibitors have shown impressive effects in reducing major vascular events in several randomized controlled trials (RCTs). The purpose of this study was to perform a meta-analysis to evaluate the effect of SGLT2 inhibitors on the risk of stroke and its subtypes. All data from prospective RCTs up to 20 October 2020 involving SGLT2 inhibitors that reported stroke events as the primary endpoint or safety in subjects with type 2 diabetes were subjected to meta-analysis. Five eligible RCTs (EMPA-REG, CANVAS, DECLARE-TIMI 58, CREDENCE and VERTIS CV) involving 46,969 participants were included. Pooled analysis of the RCTs showed no significant effect of SGLT2 inhibitors on total stroke [risk ratio (RR) = 0.95; 95% confidence interval (CI) 0.79–1.13, P = 0.585]. Subgroup analysis indicated that SGLT2 inhibitors had no significant effect against fatal stroke, non-fatal stroke, ischemic stroke or transient ischemic attack. When only hemorrhagic stroke was included, SGLT2 inhibitors were associated with a significant 50% reduction compared with placebo (RR = 0.49, 95% CI 0.30–0.82, P = 0.007). This meta-analysis shows that SGLT2 inhibitors have a neutral effect on the risk of stroke and its subtypes but a potential protective effect against hemorrhagic stroke.